Mechanisms underlying the pathogenesis of urinary bladder instability: new perspectives for the treatment of reflex incontinence - Callsen-Cencic, Peter; Mense, Siegfried (Restorative neurology and neuroscience, 1999)
The urine storage ability of the urinary bladder is markedly impaired following inflammation of the urinary bladder and spinal cord injury because of a hyperexcitability of micturition reflexes. Using two rat models of inflammation-induced bladder ov